Epidemiología y control de enfermedades febriles anemizantes en los équidos en Colombia - Benavides Ortíz, Efraín; Rodriguez Quenza, Luis Ernesto (Spei Domus, 2014)
The feverish anemia illnesses of the equidae in the tropic gather to infectious processes by diverse etiologies, which have fever as common denominator, associated with alterations in the sanguineous or reticular endothelial system. Infectious agents, generally transmitted by arthropods (flies and ticks), are the primary cause, including protozoa (Babesiosis and Trypanosomosis), bacterias (rickettsias) and the Equine Infectious Anemia viruses (EIA). Due to the fact they associate with blood, these organisms are known as hemoparasites. Available information about the topic is very limited within the country; however we offer practical information regarding diagnosis, control and prevention of these illnesses and urgent necessities of epidemiological investigation required to understand in a better way, the behavior of these pathologies. For example, there isn’t information about Babesia spp gender which affects horses in the country; it is not clarified if both species, Babesia caballi or Babesia (Theileria) equi exists in Colombia and which type of clinical reaction provokes its presence in equidae subject to several nutrition grades; neither it is known if for these species the phenomenon of enzootic stability happens. On the other hand, it is clear that Trypanosoma evansi is an important pathogen in the Oriental Plains, but till the moment there isn’t any recommendation looking forward for the control and prevention of the illnesses produced by these parasites in the region. Finally the EIA virus is endemic in the low tropic of Colombia and although some epidemic studies on its prevalence have been carried out, information with epidemic basement is still required to design a control program.